2019
DOI: 10.1371/journal.pone.0210095
|View full text |Cite
|
Sign up to set email alerts
|

Phantom Phone Signals in youths: Prevalence, correlates and relation to psychopathology

Abstract: The term Phantom Phone Signals (PPS) refers to the perception of a mobile phone ringing, vibrating and blinking when in fact it did not. Data in youth are lacking, and controversies exist on whether PPS is related to psychopathology. In the present study, we showed data on the prevalence of PPS in a population (N = 2959) of students aged 10 to 14 years. We also explored the possible association between PPS and emotional or behavioural problems. Our results showed that PPS is a relatively common phenomenon with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…Phantom phone signals (PPS) is a new symptom identified in this study. Similar to studies on mobile phones [30, 31], this study defines PPS as an individual’s illusory perception of a phone signal indicating an incoming call, message, or social media notification when no such signal is transmitted in reality. Twenty-one young employees reported that they have experienced phantom vibration or ringing when nobody has called or texted them.…”
Section: Resultsmentioning
confidence: 99%
“…Phantom phone signals (PPS) is a new symptom identified in this study. Similar to studies on mobile phones [30, 31], this study defines PPS as an individual’s illusory perception of a phone signal indicating an incoming call, message, or social media notification when no such signal is transmitted in reality. Twenty-one young employees reported that they have experienced phantom vibration or ringing when nobody has called or texted them.…”
Section: Resultsmentioning
confidence: 99%
“…Phantom phone signals refer to phantom vibration (PV) and phantom ringing (PR) of the mobile phone. The essence of the phenomenon lies in experiencing individual vibrations, hearing their phone ring or seeing the phone light up when it does not actually take place [ 10 ]. The term phubbing is a neologism resulting from the combination of the words phone and snubbing and refers to the disregard of the interlocutor in the social environment for the benefit of using a mobile phone.…”
Section: Introductionmentioning
confidence: 99%
“…or the absence of vibrations with "it's ringing" (a "false alarm") i.e. Phantom vibration and ringing syndrome are caused by second type of mismatch [12]. Phantom vibrations and ringing may be attributed to brain's ability to Phantom syndrome symptoms on a monthly basis, while some on weekly or daily basis [4].…”
Section: Discussionmentioning
confidence: 99%
“…However, the brain could mismatch actual vibrations with “it’s not ringing” (a “miss”), or the absence of vibrations with “it’s ringing” (a “false alarm”) i.e. Phantom vibration and ringing syndrome are caused by second type of mismatch [ 12 ]. Phantom vibrations and ringing may be attributed to brain’s ability to build new connections in reaction to changes in the environment, according to neuroplasticity theory.…”
Section: Discussionmentioning
confidence: 99%